Cyber security risks for minors: a taxonomy and a software architecture - Tsirtsis, Andreas; Tsapatsoulis, Nicolas; Stamatelatos, Makis; Papadamou, Kostantinos; Sirivianos, Michael (My University, 2016)
The explosion of the Internet provides a variety possibilities for communication, finding information and many other activities, turning into an essential tool in our modern everyday life. However, its huge expansion globally has created some serious safety issues, which require a special approach. One of these issues and perhaps the most important one concerns the safety of children on the Internet, as they are more exposed to dangers and threats in comparison with adults. In order to design effective measures against these threats and dangers deep understanding of minors' activities on the Internet, along with their motivation, is a first necessary step. It is shown in this report that minors' Internet activity tends heavily, and in an increasing manner, towards Online Social Networks (OSN). Thus, Internet filtering techniques designed and applied so far for child online protection need to be reconsidered and redesigned in a smarter way such as data analytics, advanced content analysis and data mining techniques are incorporated. OSN fake account identification, sexual content detection and flagging of multiple OSN accounts of the same person are examples that require such sophisticated techniques. This study deals with a literature review concerning the Internet activity and motivation of use by minors and presents in a coherent manner the identified risks and threats that children using the web and online social networks are exposed to. It also presents a systematic process for designing and developing modern and state of the art techniques to prevent minors' exposure to those risks and dangers.
Keywords: Cybersecurity risks; Minors; Online social networks; Online threats; Privacy; Taxonomy